If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3(x + 1) = -1 Reorder the terms: 2x + -3(1 + x) = -1 2x + (1 * -3 + x * -3) = -1 2x + (-3 + -3x) = -1 Reorder the terms: -3 + 2x + -3x = -1 Combine like terms: 2x + -3x = -1x -3 + -1x = -1 Solving -3 + -1x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = -1 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = -1 + 3 -1x = -1 + 3 Combine like terms: -1 + 3 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 15x+24=16x-72 | | h^2+h-72=0 | | 27x+35=15x+108 | | -2x+10x-125=83 | | 16-9t=47 | | 11x+4=2x-9 | | F(-3)=9+12(-3) | | a+w=250 | | 5b+7=2b+5 | | 13+7x=9x+5 | | 6x+3x-100=80 | | 12x-101-5x-19=6 | | 22x+4=23x+1 | | -2(x-9)+3x=9 | | -2x-9=12 | | 2(y+2)=5(y-1) | | 55x=125 | | 9x+6y=-33 | | F(x)=9+12 | | (-12n+6)+(4n-12)= | | 2x+4x-72=66 | | 5x+2=3x+39 | | 6-3y=5(2-y) | | 3x-24+2x=4x-11 | | (3x)+(x+10)+(2x-40)=180 | | 5x-7=9y | | 3x+7=2(x-5) | | y=.90(3000)+2000 | | -4x+5x-19=6 | | 12x-36+20-8x=42-2x | | 8l-1=2l+9 | | 35-3g=14 |